1996
DOI: 10.1063/1.116298
|View full text |Cite
|
Sign up to set email alerts
|

Photo-oxidation of electroluminescent polymers studied by core-level photoabsorption spectroscopy

Abstract: The C 1s and O 1s core-level photoabsorption spectra of poly͓2-methoxy,5-͑2Ј-ethyl-hexoxy͒-1,4-phenylene vinylene͔ ͑MEH-PPV͒ before and after exposure O 2 and broadband visible light were recorded to determine the degradation pathway for this polymer. The change in the O 1s spectra as a function of exposure demonstrates that the O adds to the polymer chain to form a carbonyl group. Exposure to only O 2 or only light causes no change in the C 1s or O 1s spectra. In the C 1s spectra, the change in the dependence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
51
0
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(54 citation statements)
references
References 8 publications
1
51
0
2
Order By: Relevance
“…The mechanism involves the binding of oxygen atoms to vinyl bonds, which breaks the conjugation and leads to the formation of carbonyl groups [13,12]. Spectroscopic ellipsometry studies showed that during simultaneous exposure to air and light, the thickness of the active layer increases while its refractive index and absorption coefficient drastically decrease [14].…”
Section: Degradation Of Organic Solar Cellsmentioning
confidence: 98%
See 1 more Smart Citation
“…The mechanism involves the binding of oxygen atoms to vinyl bonds, which breaks the conjugation and leads to the formation of carbonyl groups [13,12]. Spectroscopic ellipsometry studies showed that during simultaneous exposure to air and light, the thickness of the active layer increases while its refractive index and absorption coefficient drastically decrease [14].…”
Section: Degradation Of Organic Solar Cellsmentioning
confidence: 98%
“…Conjugated polymers such as poly(p-phenylene vinylene) (PPV) are known to be rather unstable in air [11], being particularly susceptible to photodegradation induced by oxygen and moisture [12]. The mechanism involves the binding of oxygen atoms to vinyl bonds, which breaks the conjugation and leads to the formation of carbonyl groups [13,12].…”
Section: Degradation Of Organic Solar Cellsmentioning
confidence: 99%
“…Successful introduction of products into the market can be hampered by limited stability during processing and device operation, [11] and improved understanding of the degradation of active components in existing devices is consequently critical for the long-term success of emerging plastic electronics and putative (supra)molecular electronics. Many techniques have been applied to studies in this area; [12][13][14][15][16] in this work, the monodispersity and exceptionally high levels of oligomer purity available allow us to use matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF-MS) as the main probe; this and related powerful analytical techniques have only rarely been explored in this field. [17,18] We report results on the massspectrometric analysis of the degradation products of two monodisperse defect-free oligomers, a penta(9,9-dialkylfluorene) and an oligoethyleneglycol-substituted sexithiophene, giving direct insight into the mechanism of oxidative degradation of p-conjugated materials.…”
mentioning
confidence: 99%
“…5, in which the black line represents the absorption spectrum for a sample that was not micromachined. As it can be seen, the absorption band centered at 500 nm ( → * electronic transition of MEH-PPV [30,31]) decreases with the energy of the pulse used in the micromachining [14], indicating a photobleaching of the sample upon fs-laser exposure [32,33]. Such changes in the MEH-PPV absorption spectrum have been attributed to photo-oxidation [6].…”
Section: Resultsmentioning
confidence: 90%